Nursing Supports for Managing Nausea and Vomiting in Patients with Cancer Having a Prognosis of Months or Weeks: A Multisite Cross-Sectional Study of Palliative Care Nurses in Japan - Masamitsu Kobayashi; Kohei Kajiwara; Kimiko Nakano; Yusuke Kanno; Miharu Morikawa; Yoshinobu Matsuda; Jun Kako (Palliative Medicine Reports)
Purpose: This study aimed to clarify the types of nursing support provided by palliative care unit (PCU) nurses in Japan to manage nausea and vomiting in patients with cancer who have a prognosis of months or weeks. Methods: This multisite cross-sectional study surveyed registered nurses from all 389 PCUs across Japan. Eligible participants were nurses providing direct care to patients. Data were collected via online surveys from October 2023 to March 2024. The frequency of 13 types of nursing supports for nausea and vomiting was evaluated using a five-point Likert scale, stratified by patient prognosis (months or weeks). Results: Of the 389 PCUs invited, 162 (41.6%) consented to participate. A total of 2448 nurses were invited, of which 539 (22.3%) responded. The most frequently implemented nursing supports were “avoiding unpleasant odors,” “providing shaved ice or ice chips,” “providing fresh air,” and “gargling with cold water.” These were consistently practiced by many nurses, regardless of patient prognosis. Conversely, specialized supports such as “reiki,” “acupressure,” “guided relaxation exercises,” “therapeutic touch,” and “foot reflexology” were rarely or seldom used. Conclusion: Noninvasive, simple nursing supports that do not require specialized knowledge or skills were frequently provided to patients with cancer who were experiencing nausea and vomiting, irrespective of their prognosis. However, nursing supports that require specialized knowledge and skills were rarely used. Further research is needed to evaluate the effectiveness of these nursing supports.